2013
DOI: 10.1088/0029-5515/53/7/073005
|View full text |Cite
|
Sign up to set email alerts
|

The role of temperature fluctuations in the dynamics of type-I and type-II edge localized modes at ASDEX Upgrade

Abstract: Abstract. 2D temperature measurements using the electron cyclotron emission imaging diagnostic at ASDEX Upgrade revealed a variety of temperature fluctuations associated with type-I and type-II edge localized modes (ELMs). The characteristics and dynamics of these modes, and their role in the ELM cycle, are presented. During type-I ELMs, different phases of distinct mode activity have been identified. At the onset of the ELM crash, a short lived mode is observed in the pedestal region. During the actual crash … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…ECEI measurements in the KSTAR tokamak [3] show that the ELM evolu- the ELM crash occurs. These measurements are in agreement with AUG ECEI measure-ments [4,5]. In AUG, the rotation of the ELM precursors is also found in the electron 48 diamagnetic direction but the first-expelled ELM filament is observed to reverse rotation 49 and to propagate in the ion diamagnetic direction.…”
supporting
confidence: 89%
“…ECEI measurements in the KSTAR tokamak [3] show that the ELM evolu- the ELM crash occurs. These measurements are in agreement with AUG ECEI measure-ments [4,5]. In AUG, the rotation of the ELM precursors is also found in the electron 48 diamagnetic direction but the first-expelled ELM filament is observed to reverse rotation 49 and to propagate in the ion diamagnetic direction.…”
supporting
confidence: 89%
“…The phase locked solution provides a robust route for thermal energy release. With locked phase, δP will grow large, leading to collapse of the edge pressure profile and the formation of filamentary structures [18]. This violent thermal energy eruption phenomenon corresponds to the so-called ELMy H mode.…”
mentioning
confidence: 99%
“…The highest mode amplitudes are seen for small ELMs in the mitigated regime. The reason for this is that after the transition to the small ELM regime, there are always some background temperature fluctuations present, so-called 'inter-ELM mode' [9]. The inter-ELM mode will be discussed in more details in subsection 3.8.…”
Section: Conditionally Averaged Size Of the Structuresmentioning
confidence: 99%
“…At ASDEX Upgrade it is commonly observed that above a certain threshold in density, a transition from the large type-I ELMs to much smaller ELM crashes occurs. The application of active in-vessel off-midplane saddle coils ('B-coils') [7] leads to an increase of density which cause the type-I ELMs to disappear [8] while smaller and more frequent crash events start to dominate [9]. In contrast to type-I ELMs, in the small ELM regime there is an almost continuous succession of small crashes.…”
Section: Introductionmentioning
confidence: 99%